Comparison of contrast-enhanced magnetic resonance angiography and digital subtraction angiography in the evaluation of renal artery stenosis and detecting of accessory and polar arteries - Yıldırım, Utku Mahir; Başaran, Ceyla (The European Research Journal, 2021)
Objectives: Renal artery stenosis (RAS) is the most common cause of secondary hypertension. RAS may cause renal insufficiency, uncontrolled hypertension and is associated with increased cardiovascular morbidity and mortality. We aimed to evaluate the accuracy of contrast enhanced Flash 3D Renal Magnetic Resonance Angiography (MRA) in the depiction of the RAS also detecting of accessory and polar renal arteries with intraarterial digital subtraction angiography (DSA) still serving as the reference standard. Methods: In this retrospective case-control study, we reviewed contrast enhanced Flash 3D Renal MRA and DSA of 71 patients who were suspected of having RAS and underwent DSA after MRA within 15 days. DSA was accepted as gold standart and the specificity, sensitivity and accuracy of MRA were determined. Results: Overall sensitivity and specificity values of contrast enhanced Flash 3D Renal MRA in detecting stenosis were 96.1% and 76.3% respectively. Conclusions: Contrast enhanced Flash 3D Renal MRA is a reliable noninvasive imaging modality in the diagnosis of RAS.